(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Herpetic infection is the most common cause of inflammatory disease in the cornea in European countries and complicated forms of herpetic infection are the most frequent indication for corneal transplantation. Factors which control the balance between acute and latent phases in recurrent herpetic infection are not sufficiently clear. At present, psychoemotional maladjustment is also considered to be a potential co-factor for developing the infectious process. Purpose. To study psychological features in individuals with recurrent herpetic keratitis (HK). Material and Methods. The study involved 27 patients with recurrent stromal herpetic keratitis, aged from 23 to 50. K. Leonhard–H. Shmishek’s questionnaire was used to study psychological features in the individuals with HK; the data obtained were exacted during the diagnostic interview and based on patients’ self-evaluation reports. The questionnaire diagnoses 10 types of accentuation: hyperthymic, stuck, emotive, anxious (fearful) type, pedantic, cyclothymic, disthymic, excitable, demonstrative, and exalted. Total scores of 8-12 points are within the normal range; those exceeding 8-12 points are indicative of accentuation. Results. More frequently we revealed accentuations as follows: emotive (92.5%), stuck (81%), hyperthymic (62.9%), demonstrative and pedantic (по 59,2%), cyclothymic (56%). Exalted accentuation with a high degree of expression was noted in 44.4% of the patients. 81.5% of the patients with recurrent HK had a combination of two and more accentuations, among which the emotive accentuation was dominant. Conclusion. Combinations of two or more types of character accentuation were found in 81.4% of the patients with recurrent HK and emotive accentuation was a dominant type of accentuated character (92.5%). Of a prevailing value in the psychological structure of the studied persons are accentuations which general characteristics are high lability of emotional reactions, their depth and duration, impressibility, vulnerability, empathy, and susceptibility. The study performed is not exhaustive; it is important to study also a role of the disease in developing maladaptive forms of psychological response.